Blood Gas Analysis in Aspiration Pneumonia: Acute and Chronic Aspects - Budiman Budiman; Indra Yanti J.; Alan Roland Tumbelaka (Indonesian Pediatric Society, 1999)
A retrospective cross-sectional study, was conducted between January1st 1991 until December 31st 1996, to find out the acute and chronic aspects ofchanges of blood gases in aspiration pneumonia A sample of all aspiration pneumonia patients hospitalized in Cipto Mangunkusumo Hospital, Jakarta, between January 1st, 1991 to December 31st, 1996 was selected (n=l67). Data were obtsined from the medical records. Only 65 patients were included in the srudy, from which 32 (49.2%) were males and 33 (50.8%) were females. Changes in blood gllS analysis observed were decrease in PaO, (30.8%), normal PaC02 (30.8%) and decrease in PaC02 (60%) and abnormal oxygen saturation (80% in acute cases, and 11.1% an chronic cases). The prevalence of acute aspiration pneumonia was 30.8% and chronic aspiration pneumonia was 69.2%. Tachypnea, cyanosis, tachycardia and prolonged expiration were more prominent in tbe acute aspiration pneumonia as well as oxygen saturation which was more dominant parameter. We concluded that with blood gllS analysis we would understand the natwal course of the disease whether acute or chronic.